2018
DOI: 10.3390/ma11071096
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Oxide (TiO2)/Polymethylmethacrylate (PMMA) Denture Base Nanocomposites: Mechanical, Viscoelastic and Antibacterial Behavior

Abstract: Currently, polymethylmethacrylate (PMMA) is the most popular denture base material. Most fractures of dentures that occur during function are due to its insufficient mechanical strength. The major drawbacks of PMMA are insufficient ductility, strength, and viscoelastic behavior. The purpose of this study was to evaluate a polymethylmethacrylate denture base material modified with TiO2 nanoparticles in terms of nanomechanical, creep-recovery, and relaxation. Additionally, the effects of addition TiO2 nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 44 publications
2
87
0
3
Order By: Relevance
“…Due to the photocatalytic property against microorganisms, patients will be able to maintain the hygiene of their dentures easily by exposing them to solar energy/light sources to activate the TiO 2 NP [11]. On the same way, Alrahlah et al (2018) reported a 50% and 90% decrease in bacterial cell attachment of E. faecalis and P. aeruginosa, respectively, with the mere addition of 3% TiO 2 NP [43]. Likewise, Totu et al (2017) investigated the effect of incorporating TiO 2 NP into a 3D-printed PMMA denture in an attempt to improve denture antimicrobial characteristics and found that even the small addition of 0.4% of TiO 2 NP to PMMA resulted in a nanocomposite that prevented the colonization of microorganisms and further formation of biofilm [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the photocatalytic property against microorganisms, patients will be able to maintain the hygiene of their dentures easily by exposing them to solar energy/light sources to activate the TiO 2 NP [11]. On the same way, Alrahlah et al (2018) reported a 50% and 90% decrease in bacterial cell attachment of E. faecalis and P. aeruginosa, respectively, with the mere addition of 3% TiO 2 NP [43]. Likewise, Totu et al (2017) investigated the effect of incorporating TiO 2 NP into a 3D-printed PMMA denture in an attempt to improve denture antimicrobial characteristics and found that even the small addition of 0.4% of TiO 2 NP to PMMA resulted in a nanocomposite that prevented the colonization of microorganisms and further formation of biofilm [24].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Alrahlah et al (2018) confirmed the increase in surface hardness of up to 35% with 3% TiO 2 NP addition. The values of the hardness measurements were higher at the surface of the composite resin and decreased as we move inward toward the core of the material, suggesting higher crosslinking at the surface [43]. Regarding selection of the most appropriate concentration of filler for inclusion within denture resin, results of multicriteria decision making (MCDM) method suggested that a filler content in the range of 2wt% would create a composite material with improved mechanical properties including surface hardness [34].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of silica/titania nanoparticle coating in dental prosthesis significantly reduces microbial adhesion. 32 As TiO 2 ratio increased in PMMA-TiO 2 it improved the antimicrobial behaviour of PMMA by drastically decreasing bacterial adherence. 32−33 The integration of TiO 2 Nanoparticles to PMMA reduces the porosity of the denture bases.…”
Section: Titanium Dioxide-tio 2 (Titania) Npsmentioning
confidence: 95%
“…It is not considered as a perfect material because of its bad mechanical and physical properties [1][2][3]. The main drawbacks of poly methyl methacrylate are deficient ductility, viscoelastic behavior and inferior mechanical strength [4][5][6] Rapid and quick development concepts of composite technology promoted the reinforcement of materials utilizing fibers [7][8][9]. Addition of polyethylene, glass and carbon fibers produced a significant increase in the impact strength.…”
Section: Introductionmentioning
confidence: 99%